(untitled) (AACINI - International Journal of Industrial Engineering, 2021)
The design of a procedure must be carried out according to the fulfillment of established requirements according to the purpose for which it is built, and when elaborating it there is a certain uncertainty about the viability of its application. It is reasonable to assume that during its implementation, inconveniences and / or inconsistencies arise between the actions or activities that make up the procedure. For this reason, Petri nets (RdP) are very useful when modeling the succession of actions and their relationships during the execution of a specific procedure. The objective of the work is to provide empirical evidence in favor of these work flow networks, based on the modeling and execution of a specific procedure, and subsequent implementation of it in a small manufacturing company for the determination of strategic technological resources. To do this, using the Workflow Petri net Designer (WoPeD) software, the tasks and relationships that make up the procedure are modeled, and the feasibility of full execution of all the actions that compose it is checked, based on the availability of certain resources and information and compliance with the requirements foreseen in its design. The results obtained from the RoP have made it possible to validate the correct and full operation of the designed tool, as well as guaranteeing the necessary and sufficient conditions to be executed in a number of defined states and actions, and with the projected resources and information, which It has been verified through a structural and robustness analysis of the software used. Finally, the work allowed the implementation of the procedure in a small sawmill company, where its appropriate and relevant utility for processes that enable the determination of strategic technological resources in the context of small manufacturing companies was evidenced.